Brain Iron Deposition Alterations in Type 2 Diabetes Mellitus Patients With Mild Cognitive Impairment Based on Quantitative Susceptibility Mapping - Qiuyue Zhao; Subinuer Maimaitiaili; Yan Bi; Ming Li; Xin Li; Qian Li; Xinyi Shen; Min Wu; Linqing Fu; Zhengyang Zhu; Xin Zhang; Jiu Chen; et al. (Journal of Diabetes)
ABSTRACT Background Iron is one of the most important elements in brain that may has a direct impact on the stability of central nervous system. The current study devoted to explore the alterations of iron distribution across the whole brain in type 2 diabetes mellitus (T2DM) patients with mild cognitive impairment (MCI). Methods The quantitative susceptibility mapping (QSM) technique was used to quantify the intracranial iron content of 74 T2DM patients with MCI and 86 T2DM patients with normal cognition (NC). The group comparison was performed by a voxel‐based analysis. Then we evaluated the relationships between cognitive indicators and magnetic susceptibility value (MSV) measured by QSM of the significant brain areas, which were set as the regions of interest (ROIs). In addition, we analyzed the moderation effects of grey matter volume (GMV) of the related brain areas and several metabolic and cerebrovascular factors on the associations between MSV of ROIs and cognitive characteristics. Results T2DM patients with MCI exhibited a lower MSV in the right middle temporal gyrus (MTG) compared to NC group. And in the MCI group, there were significantly negative correlations between MSV of the right MTG and several memory indexes. Furthermore, the moderation effects of GMV of the whole brain and the bilateral MTG on the relationship between MSV of the right MTG and scores of list recognition were significant. Conclusions T2DM patients with MCI had a temporary decreased iron content in the right MTG, which may partially compensate for cognitive impairment. Trial Registration: The study was registered at Clinicaltrials.gov (NCT02738671)